Algebra Formula Best way to learn

Spread the love

Algebra Formula

In below mentioned video, we elaborate basic reqirement of algebra formula and how to handle the issue.
नीचे दिए गए वीडियो में, हम बीजगणित सूत्र की बुनियादी आवश्यकता और इस मुद्दे को कैसे संभालना है, इसके बारे में विस्तार से बताया हैं।

What is Algebra?

Algebra is a specific branch of mathematics where letters and symbois are used to represent number.
बीजगणित गणित की एक विशिष्ट शाखा है जहाँ संख्याओं को दर्शाने के लिए अक्षरों और प्रतीकों का उपयोग किया जाता है।

Algebric Square Formulas of two components like a & b

1. (a + b)2 = a2 + b2 + 2ab

2. (a + b)2 = (a + b)(a + b)

3. (a – b)2 = a2 + b2 – 2ab

4. a2 – b2 = (a + b)(a – b)

5. (a + b)2 = (a – b)+ 4ab

6. (a – b)2 = (a + b)– 4ab

7. a2 + b2 = (a – b)+ 2ab

8. a2 + b2 = (a + b)– 2ab

Challenge to memorize Algebric Formulas

Without memorizing Algebric Formulas, it is absolutely impossible to score better marks in Algebra. To start Algebra, first and fonemost condition to memorize all important basic algebric formulas and students generally stuck up in memorizing process. Here we are providing you Flash card which help you to memorize the formula fast way without putting any pressure over you.
बीजगणितीय सूत्रों को याद किए बिना बीजगणित में बेहतर अंक प्राप्त करना बिल्कुल असंभव है। बीजगणित शुरू करने के लिए, सभी महत्वपूर्ण बुनियादी बीजगणितीय सूत्रों को याद करने के लिए पहली और सबसे महत्वपूर्ण शर्त और छात्र आमतौर पर याद रखने की प्रक्रिया में फंस जाते हैं। यहां हम आपको फ्लैश कार्ड प्रदान कर रहे हैं जो आपको बिना किसी दबाव के फॉर्मूला को तेजी से याद करने में भरपूर मदद करेगा।

Flash Card to memorize above 8 Formula

(a + b)2 = ?

a2 + b2 + 2ab

(a + b)(a + b)=?

(a + b)2

(a + b)(a - b)=?

a2 - b2

(a - b)2 =?

a2 + b2 - 2ab

(a + b)2 = (a - b)?...

(a - b)2 + 4ab

Question Explanation:

(a + b)2  =

Explanation    (a - b)2 + 4ab
a2 + b2 - 2ab + 4ab
a2 + b2 + 2ab
(a + b)2

 

 

(a - b)2 = (a + b)? + ..

(a + b)2 - 4ab

Question Explanation:

(a - b)2  =

Explanation (a + b)2 - 4ab
a2 + b2 + 2ab - 4ab
a2 + b2 - 2ab
(a - b)2

 

 

a2 + b2 = (a - b)?..

(a - b)2 + 2ab

Question Explanation:

a2 + b2 = (a - b)2 + 2ab
Explanation
a2 + b2 - 2ab + 2ab
= a2 - b2

a2 + b2 = (a + b)?..

(a + b)2 - 2ab

Question Explanation:

a2 + b2 = (a + b)2 - 2ab
Explanation (a + b)2- 2ab
a2 + b2 + 2ab - 2ab
= a2 + b2

Quiz on Above Algebric Formula

10

Algebra Formulas

Algebra Formula
Best way to Learn

1 / 8

(a + b)2 = ?

2 / 8

(a + b)(a - b)=?

3 / 8

(a + b)(a + b)=?

4 / 8

(a + b)2 = (a - b)?...

5 / 8

(a - b)2 =?

6 / 8

(a - b)2 = (a + b)? + ..

7 / 8

a2 + b2 = (a + b)?..

8 / 8

a2 + b2 = (a - b)?..

Algebric Formula of rest square & Cubic Formula

Here we have put 4 type of square formula with 3 symbols like x,y and z which are used in basic level math alnd cube formula which used frequently.
यहां हमने x, y और z जैसे 3 प्रतीकों के साथ 4 प्रकार के वर्ग सूत्र रखे हैं जो कि बुनियादी स्तर के गणित और घन सूत्र में उपयोग किए जाते हैं जो अक्सर उपयोग किए जाते हैं।

9. (x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2xz

10. (x + y – z)2= x2 + y2 + z2 + 2xy 2yz 2xz

11. (x y + z)2 = x2 + y2 + z2 2xy 2yz + 2xz

12. (x y z)2 = x2 + y2 + z2 2xy + 2yz 2xz

13. (a + b)3 = a3 + b3 +3a2b + 3ab2 

14. (a + b)3 = a3 + b3 + 3ab(a + b)

15.(a b)3 = a3 b3 3a2b + 3ab2   

16. (a b)3 = a3 b3 + 3ab(a b)

Flash Card Practice

Which one is correct?
(x + y + z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

1

Question Explanation:

x2 + y2 + z2 + 2xy + 2yz + 2xz

Which one is correct?
(x + y - z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

4

Question Explanation:

x2 + y2 + z2 + 2xy - 2yz - 2xz

Which one is correct?
(x - y + z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

2

Question Explanation:

x2 + y2 + z2 - 2xy - 2yz + 2xz

Which one is correct?
(x - y - z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

3

Question Explanation:

x2 + y2 + z2 - 2xy + 2yz - 2xz

Which on is correct
(a + b)3 =?
1) a3 + b3 +3a2b + 3ab
2) a3 + b3 +3ab + 3ab2
3) a3 + b3 +3a2b + 3ab2
4) a3 + b3 +3a3b + 3ab3 

3

Question Explanation:

a3 + b3 +3a2b + 3ab2

Which on is correct
(a - b)3 =?
1) a3 + b3 - 3a2b + 3ab2
2) a3 + b3 + 3ab(a - b)
3) a3 + b3 + 3ab(a + b)
4) a3 - b3 - 3a2b + 3ab2 

4

Question Explanation:

a3 - b3 - 3a2b + 3ab2 

Which on is correct
(a + b)3 =?
1) a3 + b3 +3a2b + 3ab
2) a3 + b3 + 3ab(a + b)
3) a3 + b3 +3ab + 3ab2
4) a3 + b3 + 3ab(a - b) 

2

Question Explanation:

a3 + b3 + 3ab(a + b)

Which on is correct
(a - b)3 =?
1) a3 + b3 +3a2b + 3ab
2) a3 + b3 + 3ab(a + b)
3) a3 + b3 +3ab + 3ab2
4) a3 + b3 + 3ab(a - b) 

4

Question Explanation:

a3 + b3 + 3ab(a - b)

D0

PO

Question Explanation:

PO

Know your authority on Algebric Formulas

4

Algebra Formula-2

1 / 9

Which on is correct
(a - b)3 =?
1) a3 + b3 +3a2b + 3ab
2) a3 + b3 + 3ab(a + b)
3) a3 + b3 +3ab + 3ab2
4) a3 + b3 + 3ab(a - b) 

2 / 9

Which on is correct
(a + b)3 =?
1) a3 + b3 +3a2b + 3ab
2) a3 + b3 + 3ab(a + b)
3) a3 + b3 +3ab + 3ab2
4) a3 + b3 + 3ab(a - b) 

3 / 9

Which on is correct
(a - b)3 =?
1) a3 + b3 - 3a2b + 3ab2
2) a3 + b3 + 3ab(a - b)
3) a3 + b3 + 3ab(a + b)
4) a3 - b3 - 3a2b + 3ab2 

4 / 9

Which on is correct
(a + b)3 =?
1) a3 + b3 +3a2b + 3ab
2) a3 + b3 +3ab + 3ab2
3) a3 + b3 +3a2b + 3ab2
4) a3 + b3 +3a3b + 3ab3 

5 / 9

Which one is correct?
(x - y - z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

6 / 9

Which one is correct?
(x - y + z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

7 / 9

Which one is correct?
(x + y - z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

8 / 9

Which one is correct?
(x + y + z)2 =?
1) x2 + y2 + z2 + 2xy + 2yz + 2xz
2) x2 + y2 + z2 - 2xy - 2yz + 2xz
3) x2 + y2 + z2 - 2xy + 2yz - 2xz
4) x2 + y2 + z2 + 2xy - 2yz - 2xz

 

9 / 9

D0